Method for adjusting thermal conductivity and bending strength of silicon nitride substrate
By controlling the residual amount of magnesium in the silicon nitride substrate and adjusting its thermal conductivity and bending strength, the problem of difficult to effectively adjust these physical properties in the prior art is solved, and flexible optimization of substrate performance is achieved.
Patent Information
- Application Number
- CN202380048835.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-22
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to effectively adjust the thermal conductivity and bending strength of silicon nitride substrates.
By controlling the residual amount of magnesium in the silicon nitride substrate, its thermal conductivity and bending strength are adjusted. Specific methods include adjusting the temperature of the sintering process in the preparation process, controlling the size of the sheet, and adjusting the atomic ratio of magnesium/yttrium in the ceramic additive.
Flexible adjustment of the thermal conductivity and bending strength of the silicon nitride substrate is achieved, and its physical properties can be optimized according to requirements.
Smart Images

Figure CN119403772A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for adjusting the physical properties of a silicon nitride substrate, and more particularly to a method for adjusting the thermal conductivity and bending strength of a silicon nitride substrate. Background Art
[0002] Ceramic materials with high electrical insulation and thermal conductivity can be used as heat media that quickly transfer heat generated from devices. Ceramic materials are used as substrates for devices used in transportation equipment, substrates for high integrated circuits, heat dissipation components for laser oscillators, reaction vessel components for semiconductor manufacturing equipment, and precision machine components.
[0003] In particular, ceramic substrates used in high-output power devices require high insulation, high withstand voltage, high thermal conductivity, high strength, and low dielectric constant. Ceramic substrates that meet these requirements include aluminum nitride substrates, aluminum oxide substrates, silicon nitride substrates, and the like.
[0004] Silicon Nitride (Si 3 N 4 ) substrate has high strength (500MPa to 800MPa), high toughness (5MPa·m to 8MPa·m) and excellent consistency of thermal expansion coefficient with silicon (Si). Furthermore, silicon nitride (Si 3 N 4 ) substrate has high thermal conductivity (70W / mK to 170W / mK). 3 N 4 ) substrate is suitable as a material for the next generation of high output power devices. Summary of the invention
[0005] Technical issues
[0006] The problem to be solved by the present invention is to provide a method for adjusting the thermal conductivity of a silicon nitride substrate.
[0007] Another problem to be solved by the present invention is to provide a method for adjusting the bending strength of a silicon nitride substrate.
[0008] Technical Solution
[0009] According to the concept of the present invention, a method for adjusting the thermal conductivity of a silicon nitride substrate may include the following steps: preparing a silicon nitride substrate; and adjusting the residual amount of magnesium in the silicon nitride substrate. The step of preparing the silicon nitride substrate may include the following steps: forming a slurry by mixing silicon nitride powder, a ceramic additive containing magnesium oxide, and a solvent; forming a sheet by molding the slurry; forming a stacked structure by sandwiching at least one of the sheets between a lower plate and an upper plate; performing a degreasing process on the stacked structure; and performing a sintering process on the stacked structure. The thermal conductivity of the silicon nitride substrate may be inversely proportional to the residual amount of magnesium in the silicon nitride substrate.
[0010] According to another concept of the present invention, a method for adjusting the bending strength of a silicon nitride substrate may include the following steps: preparing a silicon nitride substrate; and adjusting the residual amount of magnesium in the silicon nitride substrate. The step of preparing the silicon nitride substrate may include the following steps: forming a slurry by mixing silicon nitride powder, a ceramic additive containing magnesium oxide, and a solvent; forming a sheet by molding the slurry; forming a stacked structure by sandwiching at least one of the sheets between a lower plate and an upper plate; performing a degreasing process on the stacked structure; and performing a sintering process on the stacked structure. The bending strength of the silicon nitride substrate may be proportional to the residual amount of magnesium in the silicon nitride substrate.
[0011] Effects of the Invention
[0012] The present invention has found that the most important factor determining the physical properties (thermal conductivity and flexural strength) of the finally prepared silicon nitride substrate is the residual amount of magnesium. The present invention can easily control the final residual amount of magnesium in the preparation process of the silicon nitride substrate by various simple methods. As a result, the present invention can easily control the silicon nitride substrate to have the desired physical properties (thermal conductivity and flexural strength). BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The flowchart is used to illustrate the method for adjusting the thermal conductivity and / or bending strength of the silicon nitride substrate according to an embodiment of the present invention.
[0014] Figure 2 The flowchart is used to illustrate the method for preparing a silicon nitride substrate according to an embodiment of the present invention.
[0015] Figure 3 For illustration Figure 2 A simplified diagram of the first step.
[0016] Figures 4a to 4c For illustration Figure 2 A simplified diagram of the second step.
[0017] Figure 5 For illustration Figure 2A simplified diagram of the third step.
[0018] Figure 6 For illustration Figure 2 A simplified diagram of the fourth step.
[0019] Figure 7 For illustration Figure 2 A simplified diagram of the fifth step.
[0020] Figure 8 For illustration Figure 2 A simplified diagram of the sixth step.
[0021] Fig. 9 For illustration Figure 2 A simplified diagram of the seventh step.
[0022] Fig.10 FIG. 4 is a schematic diagram for explaining a method for adjusting the residual amount of magnesium in a silicon nitride substrate according to an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The preferred embodiments of the present invention will be described with reference to the accompanying drawings to fully understand the composition and effects of the present invention. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various forms and can be subjected to various changes. This embodiment is only provided to fully disclose the present invention through the description of this embodiment, and to fully inform the ordinary technicians of the technical field to which the present invention belongs of the scope of the invention.
[0024] In various embodiments of this specification, the terms first, second, third, etc. are used to describe various structural elements, but these structural elements should not be limited to the terms as described above. These are used only to distinguish any structural element from another structural element. The embodiments described and illustrated herein also include embodiments complementary thereto.
[0025] The terms used in this specification are used to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified in the context, the singular includes the plural. For the "comprises" and / or "comprising" used in the specification, the structural elements mentioned do not exclude the existence or addition of one or more other structural elements.
[0026] Figure 1 The flowchart is used to illustrate the method for adjusting the thermal conductivity and / or bending strength of the silicon nitride substrate according to an embodiment of the present invention.
[0027] refer to Figure 1 The method for adjusting the thermal conductivity and / or bending strength of a silicon nitride substrate of the present invention may include a step S100 of preparing a silicon nitride substrate and a step S200 of adjusting the residual amount of magnesium in the silicon nitride substrate.
[0028] As an embodiment of the present invention, the concentration of magnesium (Mg) in the silicon nitride substrate may be inversely proportional to the thermal conductivity of the silicon nitride substrate. In other words, the thermal conductivity may decrease as the concentration of magnesium (Mg) in the silicon nitride substrate increases. As an embodiment of the present invention, the concentration of magnesium (Mg) in the silicon nitride substrate may be proportional to the bending strength of the silicon nitride substrate. In other words, the bending strength increases as the concentration of magnesium (Mg) in the silicon nitride substrate increases.
[0029] In summary, according to the present invention, the thermal conductivity and / or bending strength of the silicon nitride substrate can be adjusted by controlling the residual amount of magnesium (Mg) in the silicon nitride substrate. Figures 2 to 9 The step S100 of preparing the silicon nitride substrate will be described in more detail.
[0030] Figure 2 FIG. 1 is a flow chart for illustrating a method for preparing a silicon nitride substrate according to an embodiment of the present invention. Figure 2 The method for preparing a silicon nitride substrate according to an embodiment of the present invention may include: a first step (S110), preparing a ceramic additive; a second step (S120), forming a slurry by mixing silicon nitride powder, a ceramic additive and a solvent; a third step (S130), forming a sheet by molding the slurry through a tape casting process; a fourth step (S140), forming a stacked sheet by stacking the sheets and performing a lamination process; a fifth step (S150), forming a stacked structure by sandwiching the stacked sheet SSH between a lower plate and an upper plate; a sixth step (S160), performing a degreasing process on the stacked structure; and a seventh step (S170), performing a sintering process on the stacked structure.
[0031] Figure 3 For illustration Figure 2 A simplified diagram of the first step.
[0032] refer to Figure 2 and Figure 3 , a first ball BA1 and a first mixture MI1 may be provided in a first container CON1. The first mixture MI1 may include ceramic powder and a solvent. Specifically, the first ball BA1 and a solvent may be placed in the first container CON1. Ceramic powder may be added to the solvent. The first ball BA1 may include ceramics such as zirconium oxide. The solvent is an organic solvent, for example, may include ethanol. The ceramic powder may include yttrium oxide (Y 2 O 3 ) and magnesium oxide (MgO).
[0033] The ceramic powder may be uniformly mixed in the first mixture MI1 by mixing the first mixture MI1 using a mixing device. The first ball BA1 may physically help the ceramic powder to be uniformly mixed. Specifically, the yttrium oxide powder and the magnesium oxide powder may be uniformly mixed in the first mixture MI1.
[0034] After the mixing is completed, the first ball BA1 may be removed. All solvents may be evaporated by drying the first mixture MI1. As a result, a ceramic additive SA in powder form may be obtained (S110). The ceramic additive SA may include yttrium oxide (Y 2 O 3 ) and magnesium oxide (MgO).
[0035] As an embodiment of the present invention, the ceramic additive SA can be composed only of yttrium oxide (Y 2 O 3 ) and magnesium oxide (MgO). As another embodiment of the present invention, in addition to yttrium oxide (Y 2 O 3 ) and magnesium oxide (MgO), the ceramic additive SA may also include additional oxides (eg, zirconium oxide).
[0036] The above yttrium oxide (Y 2 O 3 ) with respect to the ceramic additive SA may be in a mass ratio of 0.3 to 0.5. The mass ratio of the above-mentioned magnesium oxide (MgO) to the ceramic additive SA may be in a mass ratio of 0.5 to 0.7. In the ceramic additive SA, the atomic ratio of magnesium (Mg) to yttrium (Y) may be in a range of 1 to 5. More specifically, the atomic ratio of magnesium (Mg) to yttrium (Y) may be in a range of 2 to 5. In other words, the number of magnesium atoms in the ceramic additive SA may be 1 to 5 times the number of yttrium atoms, and more specifically, may be 2 to 5 times.
[0037] Figures 4a to 4c For illustration Figure 2 A simplified diagram of the second step.
[0038] refer to Figure 2 and Figure 4a , a solvent SV and a second ball BA2 may be provided into the second container CON2. The solvent SV is an organic solvent, for example, may include isopropyl alcohol and toluene. Isopropyl alcohol and toluene may be mixed in a volume ratio of 4:6. The second ball BA2 may include silicon nitride.
[0039] Silicon nitride (Si 2 O) can be added to the solvent SV in the second container CON2. 3 N 4) powder (SNP), ceramic additive SA and dispersant DIS are used to prepare the second mixture MI2. The ceramic additive SA can be prepared by the above-mentioned first step (S110). The dispersant DIS can use a commercially available dispersant DIS, for example, BYK-111 can be used.
[0040] The solvent SV may have 40 to 60 Vol% relative to the total volume of the second mixture MI2. The silicon nitride powder (SNP) may have 15 to 25 Vol% relative to the total volume of the second mixture MI2. The ceramic additive SA may have 5 to 10 wt% relative to the mass of the second mixture MI2. More specifically, the ceramic additive SA may have 5 to 7 wt% relative to the mass of the second mixture MI2.
[0041] When the content of the ceramic additive SA in the second mixture MI2 is greater than 10 wt%, the physical properties (e.g., thermal conductivity) of the prepared silicon nitride substrate are significantly reduced. Also, the purity of the silicon nitride substrate may be reduced. Therefore, the addition amount of the ceramic additive SA may be strictly limited to 5 wt% to 10 wt%, more preferably 5 wt% to 7 wt%.
[0042] The second mixture MI2 may be uniformly mixed by performing a first ball milling process on the second mixture MI2. The second ball may physically help the second mixture MI2 to be uniformly mixed.
[0043] Specifically, the first ball milling process may include rotating a second container containing the second mixture MI2 at a specified speed using a ball mill. When the second container rotates, mechanical crushing and uniform mixing can be performed by the second ball in the second container. The rotation speed of the ball mill may be 100 rpm to 500 rpm.
[0044] refer to Figure 2 and Figure 4b, after the first ball milling process, a third mixture MI3 can be prepared by adding a binder BI and a plasticizer PL to the second mixture MI2. The binder BI may include at least one of cellulose derivatives such as ethyl cellulose, methyl cellulose, nitrocellulose, carboxy cellulose, resins such as polyvinyl alcohol, acrylate, methacrylate, polyvinyl butyral, and mixtures of the above derivatives and the above resins. For example, the binder BI may include polyvinyl butyral (PVB). The plasticizer PL may include dibutylphthalate or deoctyl phthalate. The mass of the added plasticizer PL may be about 50% of the mass of the added binder BI. Further, a solvent may be added to the second mixture MI2.
[0045] The third mixture MI3 may be uniformly mixed by performing a second ball milling process on the third mixture MI3. The third mixture MI3 may be uniformly mixed by the second ball milling process to form a slurry SL (S120). The second ball milling process may be substantially the same or similar to the first ball milling process described above. Then, the second ball may be removed.
[0046] refer to Figure 2 and Figure 4c The volatile gas may be removed from the slurry SL by aging the slurry SL formed by the second ball milling process. While the slurry SL is aging, the slurry SL may be stirred using the stirrer SIT. The aging may be performed for about 24 hours.
[0047] Figure 5 For illustration Figure 2 A simplified diagram of the third step.
[0048] refer to Figure 2 and Figure 5 , the slurry SL prepared in the second step (S120) can be molded by a tape casting process to form a sheet SH (S130). Specifically, in the tape casting process, the slurry SL can be poured on a blade set to a specified dam height, and the slurry SL can be applied to a moving substrate film. The sheet SH molded body can be obtained by volatilizing the solvent from the slurry SL applied to the substrate film and peeling it off. The above-mentioned substrate film can use a stainless steel belt, an oil paper belt, or a polymer belt such as polyester fiber. For example, the slurry SL can be poured on a scraper set to a dam height of about 0.3 mm, and the slurry SL can be applied to a substrate film moving at a specified speed (for example, 0.1 m / min to 1 m / min). Then, the sheet SH can be obtained by performing a drying process and a process of peeling off the substrate film.
[0049] The tape casting process may be performed at a temperature of 30° C. to 80° C. The sheet SH formed by the tape casting process may be cut into a suitable size. The thickness of the sheet SH may be 0.1 mm to 0.16 mm.
[0050] The sheet SH may have a size of M×N. The M and N may be 60 mm to 300 mm, respectively, but are not particularly limited. That is, M and N may be changed according to the size of the desired substrate.
[0051] Figure 6 For illustration Figure 2 A simplified diagram of the fourth step.
[0052] refer to Figure 2 and Figure 6 , the plurality of sheets SH prepared in the third step (S130) may be stacked. A stacked sheet SSH may be formed by performing a lamination process on the stacked sheets SH (S140). For example, the stacked sheet SSH may be formed by stacking 3 to 5 sheets SH. The lamination process may be performed at a pressure of about 10 MPa and a temperature of about 60°C.
[0053] The laminated sheet SSH may be pressurized. The pressurization process may utilize a warm isostatic press (WIP). The pressurization process may be performed at a pressure of about 30 MPa and a temperature of about 70° C. Finally, the laminated sheet SSH may have a thickness (TH) of 0.3 mm to 4 mm.
[0054] The stacked sheet SSH is formed by stacking the sheets SH, and the size of the stacked sheet SSH may be substantially the same as the size of the sheets SH. In other words, the stacked sheet SSH may have a size of M×N. The M and N may be 60 mm to 300 mm, respectively.
[0055] Figure 7 For illustration Figure 2 A simplified diagram of the fifth step.
[0056] refer to Figure 2 and Figure 7 , a stacked structure SS may be prepared. The stacked structure SS may include a lower plate (PLT1), an upper plate (PLT2), and a stacked sheet SSH inserted therebetween. The step of preparing the stacked structure SS may include a step of sandwiching the stacked sheet SSH prepared in the fourth step (S140) between the lower plate (PLT1) and the upper plate (PLT2) (S150). Figure 7, one stacking sheet SSH is inserted between the lower plate (PLT1) and the upper plate (PLT2), but the present invention is not limited thereto. For example, two or more stacking sheets SSH may be inserted between the lower plate (PLT1) and the upper plate (PLT2).
[0057] Before preparing the stacked structure SS, boron nitride (BN) may be uniformly applied on the stacked sheet SSH. The lower plate (PLT1) and the upper plate (PLT2) may contain boron nitride.
[0058] Figure 8 For illustration Figure 2 A simplified diagram of the sixth step.
[0059] refer to Figure 2 and Figure 8 , the stacked structure SS prepared in the fifth step (S150) can be subjected to a degreasing process (Binder Burn Out, BBO) (S160). Thus, all organic substances such as binders, dispersants and plasticizers in the stacked sheet SSH can be incinerated and removed. The degreasing process can be performed in an atmospheric furnace (AF) at a temperature of about 600°C for about 12 hours. That is, the degreasing process can be performed under atmosphere (air).
[0060] Fig. 9 For illustration Figure 2 A simplified diagram of the seventh step.
[0061] refer to Figure 2 and Fig. 9 , after the sixth step (S160), a stacked structure SS may be provided in the crucible CRU. The pad powder BNP may be placed in the crucible CRU so that the stacked structure SS is buried in the pad powder BNP. The pad powder BNP may include boron nitride powder, silicon nitride powder, or a mixture thereof. When the pad powder BNP includes a mixture of boron nitride powder and silicon nitride powder, the boron nitride powder and the silicon nitride powder may be mixed in a ratio of 1:1.
[0062] The stacked structure SS may be subjected to a sintering process (S170) by heating the crucible CRU. Thus, the stacked sheet SSH may be sintered to form a silicon nitride substrate. The sintering process may be performed at a temperature of 1700° C. to 2000° C. For example, the sintering process may be performed at a temperature of about 1900° C. for 6 hours. The sintering process may be performed under a nitrogen atmosphere. The sintered stacked sheet SSH may be obtained as a silicon nitride substrate.
[0063] Fig.10 FIG. 4 is a schematic diagram for explaining a method for adjusting the residual amount of magnesium in a silicon nitride substrate according to an embodiment of the present invention.
[0064] refer to Figure 1 , Figure 2 and Fig.10 The step S200 of adjusting the residual amount of magnesium in the silicon nitride substrate may include at least one of a step S210 of controlling the temperature of the sintering process (S170) in the preparation process of the silicon nitride substrate, a step S220 of controlling the size of the sheet in the preparation process of the silicon nitride substrate, and a step S230 of controlling the atomic ratio of magnesium (Mg) / yttrium (Y) in the ceramic additive in the preparation process of the silicon nitride substrate.
[0065] In the process of preparing the silicon nitride substrate, the step S210 of controlling the temperature of the sintering process (S170) will be described. Fig. 9 The temperature of the sintering process (S170) described can be adjusted to a temperature between 1700° C. and 2000° C. In this case, the volatilization amount (i.e., the removal amount) of magnesium (Mg) in the laminated sheet SSH can increase as the temperature of the sintering process increases. The residual amount of magnesium (Mg) in the prepared silicon nitride substrate can decrease as the temperature of the sintering process increases. In other words, the magnesium (Mg) in the prepared silicon nitride substrate can be adjusted to a desired concentration (i.e., the residual amount) by controlling the temperature of the sintering process.
[0066] The step S220 of controlling the size of the sheet SH or the stacked sheets SSH in the process of preparing the silicon nitride substrate will be described. Figure 5 and Figure 6 The size (M×N) of the sheet SH is adjusted by adjusting the size of the sheet SH. In this case, in the subsequent sintering process, the volatilization amount (i.e., the removal amount) of magnesium (Mg) can be reduced as the size of the sheet SH increases. The residual amount of magnesium (Mg) in the prepared silicon nitride substrate can be increased as the size of the sheet SH increases. In other words, the magnesium (Mg) in the prepared silicon nitride substrate can be adjusted to a desired concentration (i.e., the residual amount) by controlling the size of the sheet SH.
[0067] The step S230 of controlling the atomic ratio of magnesium (Mg) / yttrium (Y) in the ceramic additive in the process of preparing the silicon nitride substrate will be described. Figure 3 and Figure 4a The ceramic additive SA described may include yttrium oxide (Y 2 O 3 ) and magnesium oxide (MgO). As described above, the atomic ratio (Mg / Y) of magnesium (Mg) to yttrium (Y) in the ceramic additive SA may be 1 to 5, more specifically, 2 to 5. The atomic ratio (Mg / Y) of the ceramic additive SA may be controlled within the range of 1 to 5, more specifically, 2 to 5, by adjusting the ratio of yttrium oxide powder to magnesium oxide powder when preparing the ceramic additive SA.
[0068] As described above, in the slurry forming step (S120), the addition amount of the ceramic additive SA can be strictly limited to 5wt% to 7wt%. Therefore, it is difficult to increase the residual amount of magnesium (Mg) in the silicon nitride substrate by increasing the addition amount of the ceramic additive SA. However, the residual amount of magnesium (Mg) in the prepared silicon nitride substrate can be increased by increasing the atomic ratio (Mg / Y) in the ceramic additive SA. In other words, the magnesium (Mg) in the silicon nitride substrate can be adjusted to a desired concentration (i.e., residual amount) by controlling the atomic ratio (Mg / Y) in the ceramic additive SA.
[0069] The laminated sheet SSH after the sintering process, i.e., the prepared silicon nitride substrate, contains more than 99 wt % SiN, but may contain trace amounts of magnesium (Mg) and yttrium (Y) as impurities. Magnesium (Mg) and yttrium (Y) as impurities may be residues derived from the ceramic additive SA as described above.
[0070] The residual amount (or concentration) of magnesium (Mg) in a silicon nitride substrate can affect the physical properties of the silicon nitride substrate (SNS). For example, the concentration of magnesium (Mg) in a silicon nitride substrate (SNS) can have a close influence on the thermal conductivity and bending strength of the silicon nitride substrate (SNS).
[0071] As described above, the thermal conductivity of the silicon nitride substrate may be inversely proportional to the residual amount of magnesium (Mg) in the silicon nitride substrate. The flexural strength of the silicon nitride substrate may be proportional to the residual amount of magnesium (Mg) in the silicon nitride substrate. The residual amount (or concentration) of magnesium in the silicon nitride substrate may be adjusted to 2000ppm to 20000ppm. At the above-mentioned residual amount of magnesium, the thermal conductivity of the silicon nitride substrate may vary between 170W / m·K and 70W / m·K. At the above-mentioned residual amount of magnesium, the flexural strength of the silicon nitride substrate may vary between 750MPa and 1000MPa.
[0072] The silicon nitride substrate may have a size of M×N, wherein M and N may be 40 mm to 200 mm, respectively. As an embodiment of the present invention, the size of the silicon nitride substrate may be smaller than the size of the laminated sheet SSH due to the sintering process.
[0073] Experimental example
[0074] Through the present invention Figures 2 to 9A silicon nitride substrate was prepared by the preparation method described in the above. On the other hand, the temperature of the sintering process (S170) was changed to 1880°C, 1930°C and 1980°C to prepare a first substrate (Experimental Example 1), a second substrate (Experimental Example 2) and a third substrate (Experimental Example 3), respectively. The residual amount of magnesium in the first substrate, the second substrate and the third substrate was measured. In addition, the thermal conductivity and bending strength of the first substrate, the second substrate and the third substrate were measured and shown in Table 1 below.
[0075] Table 1
[0076]
[0077] Referring to Table 1, it can be confirmed that the residual amount of magnesium in the substrate decreases as the temperature of the sintering process (S170) increases. That is, it is confirmed that the residual amount of magnesium in the final silicon nitride substrate can be adjusted by controlling the temperature of the sintering process (S170). It is confirmed that the bending strength decreases as the temperature of the sintering process (S170) increases, that is, as the residual amount of magnesium decreases. It is confirmed that the thermal conductivity increases as the temperature of the sintering process (S170) increases, that is, as the residual amount of magnesium decreases. In other words, it is confirmed that the physical properties (bending strength and thermal conductivity) of the silicon nitride substrate can be controlled by adjusting the residual amount of magnesium in the silicon nitride substrate.
[0078] Through the present invention Figures 2 to 9 The silicon nitride substrate was prepared by the preparation method described in . On the other hand, the size (M×N) of the sheet was changed to 140 mm×190 mm, 100 mm×100 mm and 40 mm×40 mm to prepare the fourth substrate (Experimental Example 4), the fifth substrate (Experimental Example 5) and the sixth substrate (Experimental Example 6), respectively. The temperature of the sintering process was 2050°C. The residual amount of magnesium in the fourth substrate, the fifth substrate and the sixth substrate was measured. In addition, the thermal conductivity and bending strength of the fourth substrate, the fifth substrate and the sixth substrate were measured and are shown in the following Table 2.
[0079] Table 2
[0080]
[0081] Referring to Table 2, it can be confirmed that the residual amount of magnesium in the substrate decreases as the size of the sheet decreases. That is, it is confirmed that the residual amount of magnesium in the final silicon nitride substrate can be adjusted by controlling the cutting size of the sheet in the tape casting process. It is confirmed that the bending strength decreases as the size of the sheet decreases, that is, as the residual amount of magnesium decreases. It is confirmed that the thermal conductivity increases as the size of the sheet decreases, that is, as the residual amount of magnesium decreases. On the other hand, when comparing the larger fourth substrate (140mm×190mm) with the smaller sixth substrate (40mm×40mm), it can be confirmed that even if the silicon nitride substrate is prepared under the same conditions, the difference in the residual amount of magnesium is very large. For example, it can be confirmed that the residual amount of magnesium in the fourth substrate is about 4 times the residual amount of magnesium in the sixth substrate. That is, it is confirmed that controlling the size of the sheet can have a greater impact on adjusting the residual amount of magnesium than controlling the temperature of the above-mentioned sintering process.
[0082] Through the present invention Figures 2 to 9 The silicon nitride substrate was prepared by the preparation method described in . On the other hand, the seventh substrate (Experimental Example 7), the eighth substrate (Experimental Example 8) and the ninth substrate (Experimental Example 9) were prepared by adjusting the amount of ceramic additive added and the atomic ratio of magnesium / yttrium (Mg / Y) in the ceramic additive in the slurry preparation process. The residual amount of magnesium in the seventh substrate, the eighth substrate and the ninth substrate was measured.
[0083] Table 3
[0084]
[0085]
[0086] Referring to Table 3, it can be confirmed that even if 6 wt% of the ceramic additive is added, the actual amount of Mg added in Experimental Example 8, in which the atomic ratio of Mg / Y is larger, is greater than that in Experimental Example 7. Thus, it is confirmed that in the final silicon nitride substrate, the residual amount of magnesium in the eighth substrate is greater than that in the seventh substrate. In Experimental Example 9, 7 wt% of the ceramic additive is added, and the atomic ratio of Mg / Y is also set as high as 4.5, thereby confirming that the actual amount of Mg added is up to 1.88 wt%. As a result, the residual amount of magnesium in the final silicon nitride substrate is the largest in the ninth substrate. As a result, it can be confirmed that the residual amount of magnesium in the final substrate can be controlled by adjusting the ratio of Mg / Y in the ceramic additive.
[0087] Furthermore, the thermal conductivity and bending strength of the seventh substrate, the eighth substrate, and the ninth substrate were measured and the results are shown in Table 4 below.
[0088] Table 4
[0089]
[0090] It was confirmed that even if the other preparation processes were performed in the same manner, but only the amount of ceramic additive added and the ratio of Mg / Y were changed, the seventh substrate, the eighth substrate, and the ninth substrate had different physical properties (flexural strength and thermal conductivity). In particular, it was also confirmed that as the residual amount of magnesium increased, the flexural strength increased and the thermal conductivity decreased. As a result, it was confirmed again that the key variable for adjusting the physical properties (flexural strength and thermal conductivity) of the silicon nitride substrate was the residual amount of magnesium that finally remained.
[0091] Above, the embodiments of the present invention are described with reference to the accompanying drawings, but those skilled in the art will appreciate that the present invention can be implemented in other specific forms without changing its technical ideas or basic features. Therefore, it should be understood that the above embodiments are exemplary and not restrictive in all aspects.
Claims
1. A method for adjusting the thermal conductivity of a silicon nitride substrate, characterized in that: The steps include: preparing a silicon nitride substrate; and adjusting the residual amount of magnesium in the silicon nitride substrate, The above-mentioned steps of preparing the silicon nitride substrate include the following steps: forming a slurry by mixing silicon nitride powder, a ceramic additive including magnesium oxide, and a solvent; forming a sheet by shaping the slurry; forming a stacked structure by sandwiching at least one of the above sheets between a lower plate and an upper plate; performing a degreasing process on the laminated structure; and The stacked structure is subjected to a sintering process. The thermal conductivity of the silicon nitride substrate is inversely proportional to the amount of residual magnesium in the silicon nitride substrate.
2. The method for adjusting the thermal conductivity of a silicon nitride substrate according to claim 1, characterized in that: The step of adjusting the residual amount of magnesium in the silicon nitride substrate includes adjusting the temperature of the sintering process.
3. The method for adjusting the thermal conductivity of a silicon nitride substrate according to claim 2, characterized in that: The temperature of the sintering process is adjusted to 1700°C to 2000°C. The residual amount of magnesium in the silicon nitride substrate decreases as the temperature of the sintering process increases.
4. The method for adjusting the thermal conductivity of a silicon nitride substrate according to claim 1, characterized in that: The step of adjusting the residual amount of magnesium in the silicon nitride substrate includes the step of adjusting the size of the sheet.
5. The method for adjusting the thermal conductivity of a silicon nitride substrate according to claim 4, characterized in that: The size of the sheet is adjusted to M×N, where M and N are 60 mm to 300 mm respectively. The amount of residual magnesium in the silicon nitride substrate increases as the size of the sheet increases.
6. The method for adjusting the thermal conductivity of a silicon nitride substrate according to claim 1, characterized in that: The ceramic additives include yttrium oxide and magnesium oxide. The step of adjusting the residual amount of magnesium in the silicon nitride substrate includes adjusting the atomic ratio of magnesium to yttrium in the ceramic additive.
7. The method for adjusting the thermal conductivity of a silicon nitride substrate according to claim 6, characterized in that: The atomic ratio of magnesium to yttrium in the ceramic additive is 2 to 5. The residual amount of magnesium in the silicon nitride substrate increases as the atomic ratio increases.
8. A method for adjusting the bending strength of a silicon nitride substrate, characterized in that: The steps include: preparing a silicon nitride substrate; and adjusting the residual amount of magnesium in the silicon nitride substrate, The above-mentioned steps of preparing the silicon nitride substrate include the following steps: forming a slurry by mixing silicon nitride powder, a ceramic additive including magnesium oxide, and a solvent; forming a sheet by shaping the slurry; forming a stacked structure by sandwiching at least one of the above sheets between a lower plate and an upper plate; performing a degreasing process on the laminated structure; and The stacked structure is subjected to a sintering process. The bending strength of the silicon nitride substrate is proportional to the residual amount of magnesium in the silicon nitride substrate.
9. The method for adjusting the bending strength of a silicon nitride substrate according to claim 1, characterized in that: The step of adjusting the residual amount of magnesium in the silicon nitride substrate includes adjusting the temperature of the sintering process.
10. The method for adjusting the bending strength of a silicon nitride substrate according to claim 9, characterized in that: The temperature of the sintering process is adjusted to 1700°C to 2000°C. The residual amount of magnesium in the silicon nitride substrate decreases as the temperature of the sintering process increases.
11. The method for adjusting the bending strength of a silicon nitride substrate according to claim 1, characterized in that: The step of adjusting the residual amount of magnesium in the silicon nitride substrate includes the step of adjusting the size of the sheet.
12. The method for adjusting the bending strength of a silicon nitride substrate according to claim 11, characterized in that: The size of the sheet is adjusted to M×N, where M and N are 60 mm to 300 mm respectively. The amount of residual magnesium in the silicon nitride substrate increases as the size of the sheet increases.
13. The method for adjusting the bending strength of a silicon nitride substrate according to claim 1, characterized in that: The ceramic additives include yttrium oxide and magnesium oxide. The step of adjusting the residual amount of magnesium in the silicon nitride substrate includes adjusting the atomic ratio of magnesium to yttrium in the ceramic additive.
14. The method for adjusting the bending strength of a silicon nitride substrate according to claim 13, characterized in that: The atomic ratio of magnesium to yttrium in the ceramic additive is 2 to 5. The residual amount of magnesium in the silicon nitride substrate increases as the atomic ratio increases.
Citation Information
Patent Citations
Method for manufacturing silicon nitride substrates
CN114423723A
High-thermal conductive silicon nitride ceramic having high reliability and method of manufacturing the same
JP2007197226A
Plate-like silicon nitride sintered body and production method thereof
WO2019235593A1